Tow women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women posing together. The woman on the left has her left arm around the first woman with her hand resting on her shoulder. A beer bottle in her right hand. The second woman has her right arm over the shoulder of the first woman with her right hand resting on her shoulder. In her left hand she holds a wine glass.